Obstacles to the application of (STEM) in the teaching of mathematics in the intermediate stage from the perspective of teachers and supervisors in Asir region - Al-Qahtani, Hussain Muhammad Masoud; Al Kahlan, Thabet Saeed (Journal of Educational and Psychological Sciences, 2017)
The aim of the research is to identify the obstacles that prevent the application of STEM in the teaching of mathematics in the intermediate stage from the point of view of teachers and supervisors. The researcher used the descriptive method and the questionnaire as a tool for his research. The sample of the study consisted of (103) teachers and supervisors of mathematics in the intermediate stage in Asir region, which was chosen by the simple random method during the second semester of the year 1437/1438 AH. To collect the data, use a validated and validated questionnaire. The results revealed some obstacles to the application of STEM in the teaching of mathematics in the intermediate stage, including: the tool obtained a general average (0.98) high grade, and at the level of axes, the second axis (obstacles related to the student) the highest average (3.16) (3.01). The third axis (the obstacles related to the teacher) with an average of (2.86) and finally, the third axis (the obstacles related to the classroom environment) with an average of (2.85). In light of these results, some recommendations and proposals were presented.